2020
DOI: 10.1016/j.electacta.2020.135862
|View full text |Cite|
|
Sign up to set email alerts
|

Generalised single particle models for high-rate operation of graded lithium-ion electrodes: Systematic derivation and validation

Abstract: A derivation of the single particle model (SPM) is made from a porous electrode theory model (or Newman model) of half-cell (dis)charge for an electrode composed of uniformly sized spherical electrode particles of a single chemistry. The derivation uses a formal asymptotic method based on the disparity between the size of the thermal voltage and that of the characteristic change in overpotential that occurs during (de)lithiation. Comparison is made between solutions to the SPM and to the porous electrode theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 45 publications
0
65
0
Order By: Relevance
“…In [11] it has been compared to (vi) an approximate, simplified, reduced-order battery cell model, showing very good agreement between the two different approaches, even for relatively high discharge rates up to around 12C. An example comparison between PyBaMM, experiment and DandeLiion is shown below in §5 and further work [11,22] also verify DandeLiion against other experiments and simulations. The DandeLiion solver works very much faster than: (i) our previous MATLAB implementation of a DFN solver (which is based on ode15s with the analytic Jacobian pattern provided for the solver for increased speed); (ii) the implementation of the model in the Dymola Battery Library [18]; (iii) the implementation in COMSOL Multiphysics [19]; and (iv) than the open source implementation PyBaMM [20].…”
Section: Software Performance and Operationmentioning
confidence: 79%
See 2 more Smart Citations
“…In [11] it has been compared to (vi) an approximate, simplified, reduced-order battery cell model, showing very good agreement between the two different approaches, even for relatively high discharge rates up to around 12C. An example comparison between PyBaMM, experiment and DandeLiion is shown below in §5 and further work [11,22] also verify DandeLiion against other experiments and simulations. The DandeLiion solver works very much faster than: (i) our previous MATLAB implementation of a DFN solver (which is based on ode15s with the analytic Jacobian pattern provided for the solver for increased speed); (ii) the implementation of the model in the Dymola Battery Library [18]; (iii) the implementation in COMSOL Multiphysics [19]; and (iv) than the open source implementation PyBaMM [20].…”
Section: Software Performance and Operationmentioning
confidence: 79%
“…For the cross-verification with Dymola, the code was parametrised using the same model and battery properties as described in [21]. In [11] it has been compared to (vi) an approximate, simplified, reduced-order battery cell model, showing very good agreement between the two different approaches, even for relatively high discharge rates up to around 12C. An example comparison between PyBaMM, experiment and DandeLiion is shown below in §5 and further work [11,22] also verify DandeLiion against other experiments and simulations.…”
Section: Software Performance and Operationmentioning
confidence: 99%
See 1 more Smart Citation
“… 86 Although shorter interelectrode distances reduce the barriers to high-rate operation by raising the mass-transfer-limited current, physics-based simulations similar to the one deployed here have shown that practical cell geometries are susceptible to severe concentration gradients that can swing from the equilibrium composition by ±100% under reasonable power loads. 87 …”
Section: Voltammetric Validationmentioning
confidence: 99%
“…This in turn informs practical design choices for key cell parameters (such as current collector thickness or tab placement) in order that the cell discharge uniformly. Our systematic analysis also makes clear that the simplifications are independent of the model used for the through-cell current, so that they can be combined with other through-cell asymptotic simplifications (e.g., reducing the DFN to the single particle model with electrolyte [23,32]) in a systematic and mathematically consistent way. This idea is exploited in [24], in which further model reductions are considered in various interesting and physically relevant limits.…”
Section: Discussionmentioning
confidence: 96%